XIII–XIV amžiaus Kernavės keramika - Baltramiejūnaitė, Dovilė (Archaeologia Lituana, 2017)
Pottery in Kernavė from the 13th–14th CenturiesThe subject of this study is medieval wheel-turned pottery in Kernavė in the 13th-14th centuries. The main goal is to examine the development of pottery in this medieval town. For the study, the technological, morphological and ornamental properties of pottery were analyzed in detail in search of their functional significance and developement throughout space and time. Stylistic vessel groups were established based on specific characterizing attributes. The analysis of dispersion of these vessels and their fragments reveals therole and evolution of pottery in the early urban society.
Keywords: Kernave; the Middle Ages; wheel-turned pottery; ceramic craft